2009
DOI: 10.1002/asia.200800354
|View full text |Cite
|
Sign up to set email alerts
|

New Wnt/β‐Catenin Signaling Inhibitors Isolated from Eleutherine palmifolia

Abstract: Aberrant Wnt/beta-catenin signaling has recently been implicated in tumorigenesis. On the basis of our screening program targeting inhibition of TCF/beta-catenin transcriptional activity, a plant extract of Eleutherine palmifolia was selected as a hit sample. Activity-guided fractionations led to the isolation of 15 naphthalene derivatives (1-15), including 4 new glucosides, eleutherinosides B-E (1-4), and 10 of the 15 compounds showed strong activities with high viability among 293T cells. Our data showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 24 publications
0
49
0
Order By: Relevance
“…Also, dammarane-type triterpene sapogenin (20(S)-25-OCH3-PPD; PPD25) isolated from the leaves of Panax notoginseng exerts its anticancer effect by targetting β-catenin signaling, suggesting that PPD25 may have potential as a chemotherapeutic and/or chemopreventive agent for colon and lung cancer [47]. A plant extract of Eleutherine palmifolia led to a significant decrease in the level of nuclear beta-catenin protein, resulted in the inhibitory effect on the transcription of TCF/beta-catenin in SW480 colon cancer cells in a dose-dependent manner together with selective cytotoxicity against three colorectal cancer cell lines [48]. Luteolin-7-O-Glucoside induced apoptosis by scavenging ROS and suppressing the expression of β-catenin in COLO 320 DM cells and effectively inhibited ACF development in DMH-induced experimental carcinogenesis [15].…”
Section: Discussionmentioning
confidence: 99%
“…Also, dammarane-type triterpene sapogenin (20(S)-25-OCH3-PPD; PPD25) isolated from the leaves of Panax notoginseng exerts its anticancer effect by targetting β-catenin signaling, suggesting that PPD25 may have potential as a chemotherapeutic and/or chemopreventive agent for colon and lung cancer [47]. A plant extract of Eleutherine palmifolia led to a significant decrease in the level of nuclear beta-catenin protein, resulted in the inhibitory effect on the transcription of TCF/beta-catenin in SW480 colon cancer cells in a dose-dependent manner together with selective cytotoxicity against three colorectal cancer cell lines [48]. Luteolin-7-O-Glucoside induced apoptosis by scavenging ROS and suppressing the expression of β-catenin in COLO 320 DM cells and effectively inhibited ACF development in DMH-induced experimental carcinogenesis [15].…”
Section: Discussionmentioning
confidence: 99%
“…Activity-guided fractionations led to the isolation of 15 naphthalene derivatives (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15), including 4 new glycosides, eleutherinosides B-E (1-4), and 10 of the 15 compounds showed strong activities with high viability among 293T cells, whose data showed that 2 and 9 inhibited the transcription of TCF/beta-catenin in SW480 colon cancer cells in a dosedependent manner and selective cytotoxicity against three colorectal cancer cell lines. In addition, treatment with 9 led to a significant decrease in the level of nuclear beta-catenin protein, suggesting this reduction to have resulted in the inhibitory effect of 9 on the transcription of TCF/beta-catenin [23].…”
Section: Natural Products With Anti-inflammatory and Anti-tumor Activitymentioning
confidence: 98%
“…However, there are not many effective Wnt signal inhibitors. We have also reported natural products or their derivatives that act as Wnt signal inhibitors, such as bisindole alkaloid cis-dihydroarcyriarubin C, 48) and the new natural products eleutherinoside B-E. 49) Luo et al reported the first total synthesis of 21, 4R-epimer and other derivatives by intramolecular lactamization at the N5-C6 amide bond, 50) and found moderate Wnt inhibition in 4-epi-melleumin B and 4-epi-deoxymelleumin A. We also succeeded in the total synthesis of melleumin A (21) and its 3R-epimer (26).…”
Section: Synthesis and Evaluation Of Small Molecules Based On Naturalmentioning
confidence: 99%